Polskojęzyczne podręczniki i komentarze do skodyfikowanego prawa małżeńskiego Kościoła Łacińskiego i Kościołów Wschodnich Część I - Góralski, Wojciech (Ius Matrimoniale, 2016)
Although marital law was attracting particular attention of the doctrine from the very beginning of its creation (as a field of science), only the promulgation of codes of canon law (CIC 1917, CIC 1983, CCEO 1990) “liberated” the natural need of issuing manuals and commentaries regarding marital law. The subject of the first part of the paper are the manuals and commentaries in Polish regarding the entire marital law (substantive), from before 1917 and then those issued after 1917 – before the Second Vatican Council and after the Council. The author discusses particular manuals and commentaries in chronological order and provides their evaluation. In that period of time several comprehensive manuals and commentaries appeared (in Polish) to the marital law included in CIC by: J. Pycia, F. Bączkowicz, J. Baron, W. Stawinoga, B. Wilanowski, W. Szmyd, S. Biskupski, W. Szafrański, M. Żurowski. E. Sztafrowski.